Lumen Maintenance And Trend Predictions For Light-Emitting Diodes Using Regression Analysis - Tan, Kai Zhe (2021)
This study aims to improve the prediction of lumen maintenance life under different thermal-electrical conditions and the Eyring model is proposed in this study. The model parameters are determined by regression approach, which provides the goodness of fit of the prediction model as well as the prediction interval. Apart from this, a method to predict lumen depreciation trend for different operating conditions based on the Eyring model and regression approach is also established. The findings show that the lumen maintenance life and lumen depreciation trend predicted by the Eyring model are more accurate compared to the predictions made by Arrhenius equation and Black’s model.